Perlindungan dan upaya peningkatan penegakan hak asasi manusia (ham) di indonesia - Kusiroh, Kusiroh (Maliki Interdisciplinary Journal, 2026)
This research aims to analyze the protection and efforts to improve the enforcement of Human Rights (HAM) in Indonesia. Human rights are basic rights inherent in human nature as a gift from God that must be respected and protected by the state, law, and government for the sake of human dignity. Indonesia has strong legal instruments, such as the 1945 Constitution Articles 28A-J, Law No. 39 of 1999 concerning Human Rights, and Law No. 26 of 2000 concerning Human Rights Courts. However, implementation still faces serious challenges, including unresolved cases of gross human rights violations, weak law enforcement, and abuse of power by authorities. The discussion highlights the need to strengthen the supremacy of law, dialogic approaches, decentralization, and the increased role of institutions such as Komnas HAM. The research conclusion emphasizes the need for strong political commitment and extensive human rights education to ensure that reforms proceed on a just and humane democratic path.